Pengembangan Media Pembelajaran Digital Scrapbook Berbasis Cerita Dongeng Untuk Siswa Kelas IV Sekolah Dasar - Yuwirda Saimona; Feniareny Feniareny; Bambang Hermansah; Mega Prasrihamni (Universitas Negeri Padang, 2022)
The goal is to produce a scrapbook digital media based on fairy tale stories in the learning of Indonesian grade IV SD Negeri 235 Palembang that is valid, practical and has potential effects. This type of research uses (Reseach and Development) using the ADDIE model. The subjects in this study were grade IV elementary school students who numbered one to one as many as 4 students and small groups as many as 8 students. Data collection instruments are in the form of media validation sheets by validators, practical questionnaire sheets from students and documentation. Based on the results of the study obtained an average of 85.3% with a very valid category, from the results of the student response questionnaire, namely one to one by 89.5% and small group 87.1% with the very practical category, and the test results of the questions with the results of 86.6% with the category of very potential effects. Based on the validation results, practicality results, and potential effectiveness results, it is concluded that this scrapbook digital media is very feasible to be used in learning Indonesian